Actoprotective properties of 7’-((3-thio-4-methyl-4H-1,2,4-triazole-5-yl)methyl)theophylline derivatives - Gotsulya, A. S.; Гоцуля, Андрій Сергійович; Гоцуля, А. С. (Запорізький державний медичний університет, 2016)
The aim of this work was the study of actoprotective activity of compounds, which combine sintons of 1,2,4-triazole-3-thiol and theophylline. Materials and methods. The first time synthesized 7’-((3-thio-4-phenyl-4H-1,2,4-triazole-5-yl)methyl)theophylline derivatives have been used for the research. The systemic toxicity and the acute toxicity of the studied compounds have been performed by the rapid method of Prozorovskiy to determine the optimal conditions for dispensing substances. Experiments have been conducted on a group of white nonlinear rats, 159–221 g weight. During the study of actoprotective activity the method of forced immersion in water with a load of 10% by weight of the rats has been used. The substances were administered at a dose 1/10 of LD50, and the reference drug «Riboxin» at a dose of 100 mg/kg. The swim time was recorded in seconds. The control group of animals was used for comparison; these animals received saline solution intraperitoneally 20 minutes before immersion. The obtained results were statistically processed using the standard software package of Microsoft Office 2007 and «STATISTICA@ for Windows 6.0». Results. According to the results of conducted researches it has been established that the most active compound among the studied was 7’-((5-(2-hydroxyethylthio)-4-phenyl-4H-1,2,4-triazole-3-yl)methyl)theophylline, which increased the duration of swimming by 14.31% comparing to control group, whereas the reference drug increased it by 20.57%. It has been established that 2-((5-((theophylline-7’-yl)methyl)- 4-phenyl-4H-1,2,4-triazol-3-yl)thio)-N’-(3,4-difluorobenzylidene)acetohydrazide also increases the duration of swimming. Conclusion. The study of actoprotective activity of 13 first time synthesized compounds has been conducted. 7’-((5-(2-Hydroxyethylthio)- 4-phenyl-4H-1,2,4-triazole-3-yl)methyl)theophylline has been detected as the most active compound among the studied ones. Мета роботи – дослідження актопротекторної дії сполук, що поєднують синтони 1,2,4-тріазол-3-тіолу та теофіліну. Матеріали та методи. У дослідженнях використані вперше синтезовані похідні 7’-((3-тіо-4-метил-4H-1,2,4-тріазол-5-іл)метил) теофіліну. Для визначення оптимальних умов дозування речовин, що досліджені, попередньо визначили загальнотоксичну дію та гостру токсичність за експрес-методом Прозоровського. Досліди виконали на групі білих нелінійних щурів вагою 159–221 г. Під час вивчення актопротекторної активності використали метод примусового занурення у воду з навантаженням 10% від ваги щура. Речовини вводились у дозі 1/10 від LD50, а референс препарат рибоксин – у дозі 100 мг/кг. Час запливу реєстрували в секундах. Для порівняння використовували також контрольну групу тварин, які внутрішньоочеревинно отримували фізіологічний розчин за 20 хвилин до занурення. Дані опрацьовано статистично за допомогою стандартного пакета програм Microsoft Office 2007 та «STATISTICA@ for Windows 6.0». Результати. За результатами досліджень встановили, що найактивнішою сполукою серед досліджуваних виявився 7’-((5-(2-гідроксіетілтіо)-4-феніл-4H-1,2,4-тріазол-3-іл)метил)теофілін, який збільшував тривалість примусового плавання щурів із навантаженням порівняно з контрольною групою на 14,31%, тоді як референс препарат підвищував цей показник на 20,57%. Тривалість плавання щурів підвищував також 2-((5-((теофілін-7’-іл)метил)-4-феніл-4H-1,2,4-тріазол-3-іл)тіо)-N’-(3,4- ифлуоробензіліден) ацетогідразид. Висновки. Досліджено актопротекторну активність 13 нових синтезованих сполук. Найбільш активним виявився 7’-((5-(2-гідроксіетилтіо)-4-феніл-4H-1,2,4-тріазол-3-іл)метил)теофілін. Цель работы – исследование актопротекторной активности соединений, сочетающих синтоны 1,2,4-триазол-3-тиола и теофиллина. Материалы и методы. В исследованиях были использованы впервые синтезированые производные 7’-((3-тио-4-метил-4H- 1,2,4-триазол-5-ил)метил)теофиллина. Для определения оптимальных условий дозирования веществ, которые были исследованы, предварительно установили общетоксическое действие и острую токсичность экспресс-методом Прозоровского. Опыты выполнены на группе белых нелинейных крыс весом 159–221 г. При изучении актопротекторной активности использован метод принудительного погружения в воду с нагрузкой 10% от веса крысы. Вещества вводились в дозе 1/10 от LD50, а референс препарат рибоксин – в дозе 100 мг/кг. Время заплыва регистрировали в секундах. Для сравнения использовали также контрольную группу животных, которые внутрибрюшинно получали физиологический раствор за 20 минут до погружения. Полученные данные обработаны статистически с помощью стандартного пакета программ Microsoft Office 2007 и «STATISTICA@ for Windows 6.0». Результаты. По результатам исследований было установлено, что наиболее активным среди исследуемых соединений оказался 7’-((5-(2-гидроксиэтилтио)-4-фенил-4H-1,2,4-триазол-3-ил)метил)теофиллин, который увеличивал продолжительность принудительного плавания крыс с нагрузкой по сравнению с контрольной группой на 14,31%, тогда как референс препарат повышал этот показатель на 20,57%. Продолжительность плавания крыс повышал также 2-((5-((теофиллин-7’-ил)метил)-4-фенил-4H-1,2,4-триазол-3-ил)тио)- N’-(3,4-ди-фторбензилиден)ацетогидразид. Переход от этилового к н-пропиловому и н-бутиловому эфирам 2-(5-(теофиллин-7’-ил) метил)-4-фенил-4H-1,2,4-триазол-3-илтио)ацетатной кислоты сопровождается появлением актопротекторной активности. Выводы. Исследована актопротекторная активность 13 новых синтезированных соединений. Наиболее активным оказался 7’-((5-(2-гидроксиэтилтио)-4-фенил-4H-1,2,4-триазол-3-ил)метил)теофиллин.
Актопротективні властивості похідних 7’-((3-тіо-4-метил-4H-1,2,4-тріазол-5-іл)метил)теофіліну
Актопротекторные свойства производных 7’-((3-тио-4-метил-4H-1,2,4-триазол-5-ил)метил)теофиллина
Keywords: 1,2,4-triazoles; Theophylline; Actoprotective Properties; 1,2,4-тріазол; теофілін; актопротекторна активність; 1,2,4-триазол; теофиллин; актопротекторная активность